مجاهدة النفس عند الصوفية (Comprehensive Journal of Science, 2025)
The spiritual striving (mujāhadah) of the seeker against the self is considered the beginning of the Sufi path and the foundation of its entire structure. A seeker cannot reach the goal and ultimate realization of the spiritual path while still burdened with the remnants and traces of the ego; therefore, these traces must be cast off, and the self must be abandoned entirely so that the seeker may become free from the domination of the ego.Thus, mujāhadah represents the very first step and the path toward guidance. It is comparable to ritual purification before prayer: just as there is no prayer without purification, there is no spiritual journey without mujāhadah.Mujāhadah constitutes the practical dimension of Sufi life — or, in other words, its religious and ethical dimension. Sufism in its essence is a religious–moral system through which the seeker disciplines himself with sincerity, determination, and resolve. Only those endowed with strong will and firm determination are capable of following it, because it is directed against the ego and its desires, as well as against attachment to the world and its pleasures. It is a system whose core is self-sacrifice and the preference of all that belongs to God over all that belongs to the self. For this reason, the Sufi ethical system is unique in its kind and distinct from other ethical systems, because it is founded upon exclusive devotion to God — a devotion inspired by the principle of sacrifice.The meaning that the Sufis are keen to emphasize is that the servant should not imagine that through mujāhadah he “earns” salvation or guidance, nor should he regard acts of obedience as deeds that obligate God to reward him, as was claimed by the Muʿtazilites. Rather, he must look to the Giver of guidance, who bestows it out of pure grace — namely, God. In this respect, the human being’s position before his Lord resembles that of a servant before his master: if the master commands the servant and the servant obeys, and the master then rewards him, it is not said that the servant has earned the reward by his obedience, for he is obliged to obey whether he is rewarded or not. Rather, the reward is a gift granted by the master out of generosity, even if it appears outwardly as a recompense associated with obedience